Pemanfaatan WhatsApp dalam Pemantauan Pola Tumbuh Kembang Bayi dan Balita Masa Pandemi Covid-19 - Islah Wahyuni (LPPM Akbid Harapan Ibu Pekalongan, 2021)
The first 1000 days of a child's life determine their future health. Growth monitoring in infants and toddlers aims to find early growth problems in infants and toddlers. As a result of the Covid-19 pandemic, many posyandu were closed and services for monitoring the growth and development of infants and children were neglected. The purpose of this activity is to identify growth and development problems for infants under five during immunization activities at the Private Midwife Practice during the pandemic. The method of implementing this activity is to provide group IEC, anthropometric measurements and group WhatsApp sharing. The result of the activity was that two babies who experienced growth delays had been given education and monitoring of body weight and length for 4 consecutive weeks with changes in their weight gain and length. The use of WhatsApp is very effective in helping improve understanding of baby growth patterns and complementary breastfeeding.